The Impact of Lipid-metabolizing Genetic Polymorphisms on Body Mass Index and Their Interactions with Soybean Food Intake： A Study in a Chinese Population - WANG, Jin Wei; TANG, Xun; LI, Na; WU, Yi Qun; LI, Shuai; LI, Jin; QIN, Xue Ying; ZHANG, Zong Xin; HU, Yong Hua; CHEN, Da Fang (Biomedical and environmental sciences, 2014)
Objective To evaluate the association of known polymorphisms in the lipid metabolic pathway with body mass index （BMI）, and estimate their interactions with soybean food intake. Methods A community-based cross-sectional survey was conducted in a Chinese Han population. BMI, soybean food intake, and single nucleotide polymorphisms of rs599839, rs3846662, rs3846663, rs12916, rs174547, rs174570, rs4938303, and rs1558861 were measured in 944 subjects. A multivariate logistic regression was used to analyze the association of the studied polymorphisms with BMIs. The expectation-maximization algorithm was employed to evaluate the extent of linkage disequilibrium between pairwise polymorphisms. The gene-environment interaction was assessed in the general multifactor dimensionality reduction model. Results The polymorphisms of rs3846662 and rs3846663 were associated with 10% highest BMIs when comparing to the 10% lowest values both in individuals and haplotype-based association tests. Although no statistically significant gene-environment interactions were found, people with the haplotype composed of C allele in rs3846662 and T allele in rs3846663 and low frequency of soybean intake had significantly hisher risk to overweight and obesity as compared with those with the haplotype consisting of T allele in rs3846662 and C allele in rs3846663 and highly frequent soybean food intake, with an odds ratio of 1.64 （95% confidence interval： 1.15-2.34, P〈0.01） after adjusting for the common confounders. Conclusion Our study has sugsested that rs3846662 and rs3846663 may be the potential candidate polymorphisms for obesity, and their effect on the pathogenesis could be mediated by the frequency of soybean food intake.